1998
DOI: 10.1002/1529-0131(199811)41:11<1995::aid-art15>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular human T cell leukemia virus type I tax protein stimulates the proliferation of human synovial cells

Abstract: Our results suggest that extracellular Tax can regulate the expression of endogenous cellular genes in synovial cells and may contribute to the NF-kappaB-mediated synovial hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…Purified, recombinant Tax protein was shown to stimulate the proliferation of PBMC [18], activation of NF-B pathway, and expression of TNF-␤, Ig light chain, and IL-2 receptor ␣ expression on lymphoid cells [19 -21]. Extracellular Tax has also been shown to induce cytokine production from adult human microglial cells [22], TNF-␣ secretion from human neuronal cells [23], and proliferation of human synovial cells [24]. Serologic evidence also supports the presence of extracellular Tax; ϳ90% of HTLV-1-infected patients have antibodies to Tax [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Purified, recombinant Tax protein was shown to stimulate the proliferation of PBMC [18], activation of NF-B pathway, and expression of TNF-␤, Ig light chain, and IL-2 receptor ␣ expression on lymphoid cells [19 -21]. Extracellular Tax has also been shown to induce cytokine production from adult human microglial cells [22], TNF-␣ secretion from human neuronal cells [23], and proliferation of human synovial cells [24]. Serologic evidence also supports the presence of extracellular Tax; ϳ90% of HTLV-1-infected patients have antibodies to Tax [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-I is known as an oncovirus which can induce ATL, and a recent report by Uchida et al including patients with ATL showed that mononuclear cells obtained from HTLV-I carriers exhibited upregulation of telomerase activity [14]. This evidence suggests that synoviocytes infected with HTLV-I have higher proliferation rates at least in part by the activation of the telomerase, since HTLV-I infection promotes the growth of synoviocytes [15,16,17]. Moreover, according to our recent data, telomerase activity is upregulated in cultured synoviocytes by adding bFGF [18].…”
Section: Discussionmentioning
confidence: 99%
“…1997). In addition, Tax encoded by HTLV‐I pX gene upregulates the expression of IL‐6 (Aono et al . 1998).…”
Section: Discussionmentioning
confidence: 99%